PENGARUH KUALITAS PRODUK, HARGA, DAYA TARIK IKLAN DAN CITRA MEREK PADA KEPUTUSAN PEMBELIAN PADA HONDA BEAT MOTORIZED VEHICLE - Dien Hawa, Sarah; Rianto, Sugeng; Saumi Andrean Nofa, Muhammad (DFAME Digital Financial Accounting Management Economics Journal, 2024)
Honda Beat Motorcycle is the most popular by most people, both young people and parents because of its stylish and simple design. This can be proven based on the results of the Top Brand Award survey which is ranked first in the Top Brand Index category as shown below. Consumers who have a positive perception of a brand, meaning that the brand has a strong impression compared to other brands. This study aims to determine the effect of Product Quality, Price, Advertising Attractiveness and Brand Image on Purchasing Decisions for Honda Beat Motorbikes. The data used in this study are primary data obtained through a questionnaire. This reseach using 97 sample who who have already used Honda beat. The analysis method used is multiple linear regression analysis. The results of the analysis show that Product Quality, Price, Advertising Attractiveness and Brand Image have a positive effect on Purchasing Decisions for Honda Beat Motorbikes.